P203 Is more better? A protocol to investigate the (neural) effects of repeated vs. single tACS in healthy and pathological ageing. Issue 3 (March 2017) - Müller-Ehrenberg, L.; Verhey, F.; Sack, A.; Jacobs, H.
Abstract : Introduction: Healthy and pathological ageing, such as Alzheimer's disease (AD), both co-occur with disruptions of neuronal activity in memory networks. A prodromal phase of AD is mild cognitive impairment (MCI). Transcranial current stimulation (tCS) has previously been implemented in various settings, showing to have beneficial influences on network connectivity. The recollection and hippocampal networks are vulnerable to AD-related pathology. Targeting these networks with tCS in an early phase may be a valid disease-delaying approach. The hippocampus cannot be stimulated directly, but is closely connected with the angular gyrus. By stimulating the angular gyrus during memory performance makes the recollection network more susceptible and therefore, we hypothesize that indirect effects might be detected in the hippocampus. Further, we will investigate the neural and cognitive effects of single vs multiple sessions. Knowledge about the (long-term) cognitive and neural mechanisms can give valuable insights and pave the ground for exploring tCS as a treatment option in future studies. Objectives: We aim to investigate the neural changes underlying tACS on the angular gyrus in MCI patients and in healthy controls using simultaneous fMRI, and the effect of repeated vs. first-session tACS. Performance on a memory task will be compared between sessions. A hippocampus-driven pattern separation memory task will be implemented to investigate if tACS vs. sham during the encoding and consolidation phase has an influence on brain activation during subsequent retrieval. Transfer to a similar, non-practiced task will be assessed at follow-up. Patients & methods or materials & methods: 20 MCI patients and 20 healthy controls will receive 1 sham-tACS session, 5 consecutive tACS-sessions, and one follow-up session. FMRI-scans will be obtained during sham, on the first and fifth active session and one week after the last active session. TACS will be applied online during encoding (task-fMRI) and consolidation (resting-state-fMRI) of a pattern separation task. Parallel task-versions will be used in randomized order to minimize learning effects. Within- and between group analyses will be conducted on both the fMRI-data (task and rs-fMRI) and the behavioural data (pattern separation performance).